Embryonal tumor with abundant neuropil and true rosettes with only one structure suggestive of an ependymoblastic rosette. (3rd September 2014) - Nobusawa, Sumihito; Orimo, Kenta; Horiguchi, Keishi; Ikota, Hayato; Yokoo, Hideaki; Hirato, Junko; Nakazato, Yoichi
<x xml:space="preserve">Abstract</x> Embryonal tumor with abundant neuropil and true rosettes (ETANTR) is a very aggressive embryonal central nervous system (CNS) tumor, histologically featuring ependymoblastic rosettes and neuronal differentiation in a neuropil‐like background. 19q13.42 amplification was identified in ETANTR and epndymoblastoma, suggesting that these tumors constitute a single entity, called embryonal tumor with multilayered rosettes (ETMR). Here, we report a case involving a 2‐year‐old boy with a pontine embryonal tumor composed of clusters of poorly differentiated neuroepithelial cells, and smaller neuroblastic/neurocytic cells in a fibrillary and paucicellular neuropil‐like matrix, where clear ependymoblastic rosettes were not detected but only one structure suggestive of an ependymoblastic multilayered rosette was found. Fluorescence in situ hybridazation analysis revealed 19q13.42 amplification, supporting the diagnosis of ETANTR. This report indicates that rare ependymoblasic rosettes found in embryonal tumors, which are otherwise CNS primitive neuroectodermal tumors or medulloblastomas, are significant for considering the examination of 19q13.42 amplification to confirm the diagnosis of ETMR.